Obtención y caracterización molecular del híbrido somático solanum tuberosum x solanum mochiquense - Chico Ruíz, Julio Róger (2011)
The "potato" is one of the oldest foods known to man managed. Its origin is Latin, probably in the Andes of southern Peru and northern Bolivia. However, its cultivation is decreasing its production problems because we have a national long-term, concerted scientific and technical basis. The techniques of in vitro cultivation of cells and tissues can assist conventional breeding to overcome barriers to sexual incompatibility genotypes of interest. Among these, the protoplast fusion technique is an alternative to generate new genetic variation and transfer desirable traits from wild species to cultivated species by interspecific somatic hybridization. With the above, the overall objective of this study was to obtain and characterize molecular somatic hybrids obtained by fusion of protoplastos. Se used in vitro plantlets 4-6 weeks of Solanum tuberosum, cultivar yungay and the wild species Solanum mochiquense. The leaves (1.0 g) of both species were treated with enzyme solutions of cellulase and pectinase for protoplasts and the fusion of the same PEG was used. The colonies formed were transferred to MS basal medium supplemented with combinations of growth regulators (NAA and BAP) Hybridization of fused regenerants was confirmed by RAPD. The results show that the cellulase enzyme solution 2% + 0.4% pectinase produced the highest number of protoplasts in both species. The highest rate of fusion was 20 ± 1.7 for 50% PEG. Treatment (0.54μM 4.43μM NAA and BAP) gave the highest callus formation (18 ± 0.7), embryos (24) and regenerated plantlets (6). In conclusion, somatic hybrids were obtained 6 products of protoplast fusion S. tuberosum x S. mochiquense, and molecularly characterized using RAPD.